Die sosiaal-wetenskaplike begrip change agent toegepas op die Efesiërbrief: "n toepassing tot kerklike welwese - Wyk, Barry J. van (HTS teologiese studies, 2017)
This article gives a short reflection on the background and origin of the social-scientific model change agent in relation to change agency, a relationship that causes an alternate state of consciousness for the change agent. Arguing from the seven-point explanation of Malina and Pilch of how a change agent operates, this article applies the model to the letter to the Ephesians. The conclusion is that this social-scientific model is helpful for the recent church to realise how narrow the relation is between Jesus Christ and the church, in view of the future of the church as a future in Christ. A choice is made to find alternate words in the Afrikaans language suitable for the theological debate, namely opdraggewer [change agency], meningsvormer [change agent] and alternatiewe staat van bewussyn [alternate state of consciousness].